2015
DOI: 10.1097/md.0000000000001879
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Genetic Polymorphisms in the Promoter Regions of Let-7 and Risk of Papillary Thyroid Carcinoma

Abstract: The aim of this study was to investigate the association between 2 polymorphisms (ie, rs10877887 and rs13293512) in the promoter regions of let-7 and the risk of papillary thyroid carcinoma (PTC).A case-control study of 618 PTC patients and 562 controls was conducted. The rs10877887 polymorphism was genotyped by using polymerase chain reaction-restriction fragment length polymorphism and the rs13293512 polymorphism was genotyped by using a TaqMan Genotyping Assay. The results were confirmed by DNA sequencing.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
0
23
1
Order By: Relevance
“…Among them, two SNPs were located into lncRNAs, and the rest were located into miRNAs. The control group of nine cohorts from six studies [ 33 , 43 , 44 , 59 , 65 , 66 ] were not in agreement with HWE ( P > 0.05). Except all the three cohorts of miR-219-1 rs213210 and two of the four cohorts of miR-26a-1: rs7372209, the rest cohorts were of different SNPs (listed in detail in Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Among them, two SNPs were located into lncRNAs, and the rest were located into miRNAs. The control group of nine cohorts from six studies [ 33 , 43 , 44 , 59 , 65 , 66 ] were not in agreement with HWE ( P > 0.05). Except all the three cohorts of miR-219-1 rs213210 and two of the four cohorts of miR-26a-1: rs7372209, the rest cohorts were of different SNPs (listed in detail in Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 95%
“…The ethnic background of the participants included Asian [ 30 , 32 , 33 , 35 38 , 42 , 44 – 51 , 53 59 , 61 69 ], Black [ 43 ], Caucasian [ 28 , 31 , 34 , 39 41 , 52 , 60 ], and mixed [ 29 , 43 ]. Several cancer types were investigated, such as oesophageal cancer [ 30 , 32 , 42 44 , 46 , 47 , 49 , 53 , 55 , 57 , 58 , 60 , 63 , 65 , 68 ], head and neck squamous cell carcinoma (HNSCC) [ 29 , 31 , 35 , 40 ], nasopharyngeal carcinoma (NPC) [ 36 , 38 , 48 , 50 , 64 ], oral squamous cell carcinoma (OSCC) [ 33 , 37 , 41 , 51 , 52 , 54 , 59 , 62 ], and thyroid carcinoma [ 28 , 34 , 39 , 45 , 56 , 61 , 66 , 67 , 69 ]. It is important to mention that four studies [ 29 , 41 , 46 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The Rs712 sequence is located on the KRAS gene 3′-UTR mutant, which is targeted by Let-7. It has been confirmed that polymorphisms in this region is associated with the risk of developing thyroid cancer [40, 41]. Rs10877887 polymorphism, which is located in the promoter region of Let-7, may be at risk of developing thyroid cancer, and rs13293512 polymorphism, which is located in the promoter region of Let-7, may be linked with lymph node metastasis in thyroid cancer [41].…”
Section: Mirna-let-7mentioning
confidence: 99%
“…It has been confirmed that polymorphisms in this region is associated with the risk of developing thyroid cancer [40, 41]. Rs10877887 polymorphism, which is located in the promoter region of Let-7, may be at risk of developing thyroid cancer, and rs13293512 polymorphism, which is located in the promoter region of Let-7, may be linked with lymph node metastasis in thyroid cancer [41]. In a study, Let-7 expression was measured in the serum of 106 patients with thyroid cancer and was compared with that of 95 patients with benign glands and 45 patients without thyroid problems.…”
Section: Mirna-let-7mentioning
confidence: 99%
“…Previous work has shown that single nucleotide polymorphisms (SNPs) in the promoters of miRNAs may modulate individual’s susceptibility to a variety of human diseases 20 21 22 23 24 25 26 27 28 29 30 . Recently, several SNPs in the promoter of miR-143/145 cluster have been identified 21 .…”
mentioning
confidence: 99%